(untitled) (Bangladesh Journal of Bioethics, 2020)
Bangladesh Bioethics Society in cooperation with National Institute of Neuro Science (NINS), Agargoan, Dhaka is going to organized 60 hours Training Course on Applied Research Methodology and SPSS on March 14-22, 2021 for the Post graduate Medical Students of NINS and Member of BBS. The course is designed to familiarize the participants with modern tools, techniques and methodologies of research to develop professional knowledge and skills in the field of Health Care System. After completion of the course, participants will be expected to undertake research projects independently and to be able to evaluate the research progress at each stage of the process. Mohammad Jainul Bari, Secretary, Planning Division, Ministry of Planning, Government of People Republic of Bangladesh will be the Chief Guest. Advisor Research & Publication, WHO Prof Dr Mohammad Mostofa Zaman, Focal Point, Gender, Equity & Rights, WHO will be the special Guest. Prof. (Dr.) Quazi Deen Mohammed, Professor of Neurology & Director, National Institute of Neuroscience will host of the programme as a Local Coordinator. This programme is funded by SSRC, Planning Division, Ministry of Planning, Government of the People’s Republic of Bangladesh. There is no registration fee. Morning Refreshment and Lunch will be provided. There is some remuneration for the participants. Interested are requested to contact Prof Shamima Pervin Lasker PhD, Professor & Head of Anatomy, Shahabuddin Medical College at splasker04@yahoo.com